Detection of female volleyball player body composition uzing bioelectric impedanse analysis: cross-sectional study - Ratko Pavlović; Vladan Savić; Nikola Radulović; Iryna Skrypchenko (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose: In today's sport, and especially in high-performance sports where volleyball also belongs, continuous monitoring of Body Composition (BC) can significantly regulate the training process, which has a positive effect on the top form of athletes. Aim of the current study was to assess and analyze the body composition of a female volleyball players VC "Jahorina", by Bioelectric Impedance Analysis (BIA). Material and methods: In study the participants consist 18 female volleyball players, the members of the  Volleyball Club ''Jahorina'' from Pale, East Sarajevo City (Body height = 173 ± 8.77 cm; Body weight = 66.04 ± 9.09kg; BMI = 22.03 ± 2.19 kg/m², decimal age 19.11 ± 2.63 years old) who competes in the Premier League of Bosnia and Herzegovina (B&H). Results: of the study showed that the body composition is within the healthy (allowed) values recommended for this population of volleyball players (Body Fat = 24.82%; Body Fat=11.44kg; Body Water = 53.68%; Body Muscle = 47.09 kg, BMR = 1538.08; DCI = 6435.38, etc.). Conclusion: Compared to the results of other authors, that Jahorina volleyball players do not lag far behind European clubs in terms of weaker BC (BF%, BFkg, BW%, BMkg, BMR, DCI, BMI, etc.). The only place where they are inferior is the body height of the volleyball player (height = 173 ± 8.77 cm), while the relative value of Body weight = 66.04 ± 9.09 kg is evident.